Interleukin (IL)-23 Stimulates IFN-γ Secretion by CD56bright Natural Killer Cells and Enhances IL-18-Driven Dendritic Cells Activation - Ziblat, Andrea; Nuñez, Sol Y.; Raffo Iraolagoitia, Ximena Lucía; Spallanzani, Raúl German; Torres, Nicolás I.; Sierra, Jessica M.; Secchiari, Florencia; Domaica, Carolina I.; Fuertes, Mercedes B.; Zwirner, Norberto W. (Frontiers in Immunology, 2018)
IL-23 is a member of the IL-12 family of cytokines that, as the other members of this family, is secreted by monocytes, macrophages and dendritic cells (DC) upon recognition of bacterial, viral and fungal components. IL-23 is critical during immunity against acute infections and it is also involved in the development of autoimmune diseases. Although immunoregulatory effects of IL-23 on mouse NK cells have been described, the effect of IL-23 on human NK cells remains ill-defined. In this study, we observed that monocytes stimulated with LPS secreted IL-23 and that blockade of this cytokine during monocyte and NK cell co-culture led to a diminished production of IFN-gamma by NK cells. Accordingly, rIL-23 induced NK cell activation and stimulated IFN-gamma production by CD56bright NK cells. This effect involved MEK1/MEK2, JNK, PI3K, mTOR and NF-kappaB, but not STAT-1, STAT-3 nor p38 MAPK pathways. Moreover, while NK cell-mediated cytotoxicity remained unaltered, antibody-dependent cellular cytotoxicity (ADCC) was enhanced after IL-23 stimulation. In addition, IL-23 displayed a synergistic effect with IL-18 for IFN-gamma production by both CD56bright and CD56dim NK cells, and this effect was due to a priming effect of IL-23 for IL-18 responsiveness. Furthermore, NK cells pre-stimulated with IL-18 promoted an increase in CD86 expression and IL-12 secretion by DC treated with LPS, and IL-23 potentiated these effects. Moreover, IL-23-driven enhancement of NK cell “helper” function was dependent on NK cell-derived IFN-gamma. Therefore, our results suggest that IL-23 may trigger NK cell-mediated “helper” effects on adaptive immunity, shaping T cell responses during different pathological situations through the regulation of DC maturation.